Bridging Classrooms and Careers: Exploring Students' Perspectives on English for Specific Purposes Instruction - Widya Syafitri; Febria Sri Artika; Muthia Rahman; Cantika Atma Triannisa (STAI Hubbulwathan Duri, 2025)
Globalization has heightened the need for English proficiency in specialized fields such as economics, hotel management, and tourism. English for Specific Purposes (ESP) courses aim to equip students with relevant language skills, but questions remain about their effectiveness and alignment with industry needs. This study investigates students’ perceptions of ESP course design and delivery across five universities in West Sumatra, Indonesia. Data were collected through surveys and interviews with 108 students, focusing on course credit hours, instructional materials, teaching strategies, and the use of technology. Findings show that 65% of students preferred interactive methods, such as simulations and case studies, over traditional lectures. Students also emphasized the need for more practical writing tasks and role-playing opportunities. Limited access to technological tools, including virtual trading platforms, was identified as a barrier to effective learning. Using Activity Theory, the study examines the interplay between students, instructional tools, institutional rules, and learning goals. It highlights challenges such as insufficient credit hours and unequal access to technology. Interactive methods and collaborative tasks emerged as effective strategies for building job-relevant language skills. Enhancing ESP programs requires increasing credit hours, integrating advanced technological tools, and aligning content with professional contexts. These recommendations aim to improve the impact of ESP education and better prepare students for global careers.